Factors Associated with Basic Immunization Status of Infants - Dewi Novitasari Suhaid; Fransisca Faranita (SEAJOM: The Southeast Asia Journal of Midwifery, 2018)
Immunization is an attempt to actively boost a person's immunity against a disease, so that if one day exposed to the disease will not get sick or just experience mild illness. Immunization is routinely divided into primary immunization and continued immunization. Basic immunization is given to infants aged 0 to 1 year, where as advanced immunization is a repeat immunization intended to maintain immunity level or to prolong the period of protection. Further immunization is given when primary immunization is given first, and is given at the age of toddlers and at school age. This research is cross-sectional study. The dependent variable in this study is the basic immunization status of infants, while the independent variables include age, education level, occupation, knowledge and attitude. The sample of this research is mothers with children aged 12-24 months totaling 250 respondents. Instrument of data collection using questionnaire and health record of baby. The data transformation uses the data normality test and Rasch model. Data analysis technique using Chi Square test and logistic regression test. The result of data analysis showed that there was a significant correlation between occupation (p <0,05, PR = 1,864; 95% CI = 1,121-3,097), education level (p <0,05; PR = 3,438; 95% CI = 1,671- 7,074), knowledge (p <0,05, PR = 2,653; 95% CI 1,580-4,455) and attitude (p <0,05, PR = 3,202; 95% CI = 1,897-5,405) with infant immunization status. Age has no significant relationship with the basic immunization status of infants. Conclusions coverage of basic infant immunization completeness in this area is still low that is equal to 42,4%. Attitude is the most dominant factor associated with the basic immunization status of infants.